Contralateral Cochlear Labyrinthine Concussion without Temporal Bone Fracture: Unusual Posttraumatic Consequence - I. M. Villarreal; D. Méndez; J. M. Duque Silva; P. Ortega del Álamo (Case Reports in Otolaryngology)
Introduction. Labyrinthine concussion is a term used to describe a rare cause of sensorineural hearing loss with or without vestibular symptoms occurring after head trauma. Isolated damage to the inner ear without involving the vestibular organ would be designated as a cochlear labyrinthine concussion. Hearing loss is not a rare finding in head trauma that involves petrous bone fractures. Nevertheless it generally occurs ipsilateral to the side of the head injury and extraordinarily in the contralateral side and moreover without the presence of a fracture. Case Report. The present case describes a 37-year-old patient with sensorineural hearing loss and tinnitus in his right ear after a blunt head trauma of the left-sided temporal bone (contralateral). Otoscopy and radiological images showed no fractures or any abnormalities. A severe sensorineural hearing loss was found in his right ear with a normal hearing of the left side. Conclusion. The temporal bone trauma requires a complete diagnostic battery which includes a neurotologic examination and a high resolution computed tomography scan in the first place. Hearing loss after a head injury extraordinarily occurs in the contralateral side of the trauma as what happened in our case. In addition, the absence of fractures makes this phenomenon even more unusual.